Territorios Americanos / American Territories - Stephannie Fell (ARQ)
"How would you define America?" ARQ’s 2025 cycle, titled "Esto es América / This is America", sets out to explore the continent through a transnational lens—beyond political borders and linguistic divides. We are interested in understanding America through shared conditions, tensions, and phenomena that cut across geographic, historical, and cultural boundaries. This issue marks the beginning of a three-part editorial series that approaches the continent from complementary angles: geography and territory (American Territories), urban density and processes of informality (Popular America), and ideological projections and collective imaginaries (Utopian America).